Problems encountered by family businesses : a Singapore context. - Lee, Chia Tien. (2008)
Our study intends to find out whether most family businesses in Singapore fail in the hands of the third generation. We also like to find out the causes of local family business failures. Do they face special challenges beyond the typical business pitfalls? To carry out this research, we have collected information on six local family businesses to be presented as case studies.